2020
DOI: 10.1186/s13690-020-00471-6
|View full text |Cite
|
Sign up to set email alerts
|

Lost in space - an exploration of help-seeking among young people with mental health problems: a constructivist grounded theory study

Abstract: Background Mental health problems among young people is a worldwide public health concern. There has been an increase in mental health problems among young people in the Nordic countries in the last 25 years, particularly in Sweden. Despite this increase, international research has repeatedly shown that young people do not access or receive support when encountering mental health problems. The purpose of this study was to explore the process of help-seeking for professional support among young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…A sheltering environment, with a professional who is interested in listening to the adolescent tell their story, increases their autonomy. Westberg Häggström et al (2020) have pointed out that adolescents are not able to access adequate help from public health services regarding their mental ill-health. However, in our study, a vast majority of the adolescents (Table 1) did gain access to both formal mental-health services and SSWs.…”
Section: Discussionmentioning
confidence: 99%
“…A sheltering environment, with a professional who is interested in listening to the adolescent tell their story, increases their autonomy. Westberg Häggström et al (2020) have pointed out that adolescents are not able to access adequate help from public health services regarding their mental ill-health. However, in our study, a vast majority of the adolescents (Table 1) did gain access to both formal mental-health services and SSWs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, not all young people have access to professional services and so families and friends are often essential helpers for youth in rural communities (Hernan et al 2010), youth experiencing marginalisation, or those who live in communities with differing conceptualisations of mental health living within a majority western culture (Freedenthal and Stiffman, 2007;De Anstiss & Ziaian, 2010;Ellis et al 2010;Valibhoy et al 2017). When young people are in a position to seek support from a formal service, informal supports play an essential role in providing resources and in assisting young people to access and stay engaged with services (Medlow et al 2010;Valibhoy et al 2017;Westberg et al 2020;Eigenhuis et al 2021).…”
Section: Informal Sources Of Help As Important Pathway Agentsmentioning
confidence: 99%
“…Research has demonstrated that social relationships are vital to young people's quality of life and that youth mental health problems are frequently connected to issues or conflict with family and friends (Gilchrist & Sullivan, 2006;Fox and Butler, 2007;Moen and Hall-Lord 2019;Westberg et al 2020). An impossible situation can arise when a young person requires both a professional helper from outside of their social networks and the emotional, financial or logistical resources provided by friends and family to access and attend a mental health service.…”
Section: Informal Sources Of Help As Important Pathway Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a shortage of psychiatrists, psychologists, nurses, and social workers ( Fricchione et al, 2012 ; Liu et al, 2017 ); almost half of the world's population live in countries where there is less than one psychiatrist per 100,000 people ( World Health Organization, 2017 ). This shortage of mental healthcare professionals restricts care opportunities, resulting in long waiting lists, delays, and multiple, diverse contacts before appropriate care is obtained ( MacDonald et al., 2018 ; Westberg et al, 2020 ).…”
mentioning
confidence: 99%